Beyond Earth: Harnessing Marine Resources for Sustainable Space Colonization - Marco F. L. Lemos (Marine Drugs)
The quest for sustainable space exploration and colonization is a challenge in its infancy, which faces scarcity of resources and an inhospitable environment. In recent years, advancements in space biotechnology have emerged as potential solutions to the hurdles of prolonged space habitation. Taking cues from the oceans, this review focuses on the sundry types of marine organisms and marine-derived chemicals that have the potential of sustaining life beyond planet Earth. It addresses how marine life, including algae, invertebrates, and microorganisms, may be useful in bioregenerative life support systems, food production, pharmaceuticals, radiation shielding, energy sources, materials, and other applications in space habitats. With the considerable and still unexplored potential of Earth’s oceans that can be employed in developing space colonization, we allow ourselves to dream of the future where people can expand to other planets, not only surviving but prospering. Implementing the blend of marine and space sciences is a giant leap toward fulfilling man’s age-long desire of conquering and colonizing space, making it the final frontier.